تعارضات المركز والهامش في ديوان الحماسة لأبي تمام (المرأة أنموذجًا) - Ahmed, م.م. صفاء علي (Tasnim International Journal for Human, Social and Legal Sciences, 2022)
This research aims at the concept of center and margin and its contradictions in the book of enthusiasm by Abi Tammam, and this book is important because it collected in its choices a large number of Arabic poetry, whether a poet or poet, and the choice came to the woman as a model for research, the research revealed the woman’s view of herself and the other. The man) sometimes as a center and sometimes as a margin, and vice versa, and these two views have been written down in the choices of this book. The research proceeded on a preamble and two axes; The preamble includes the definition of the term center and margin, and it is divided into: (the center and the margin socially, the literary center and the margin, the political center and the margin, the center and the economic margin). As for the first axis, it was entitled: (Woman as a poetic subject), and it is divided into: (Woman as the center and the woman as a marginal). While the second axis came under the title: (The Presence of the Woman Poet between the Center and the Margin), and it includes: (Women as a Center, and Women as a Margin).